Hedges and Boosters in Student Scientific Articles within the Framework of a Pragmatic Metadiscourse - Ardhianti, Mimas; Susilo, Jimat; Nurjamin, Asep; Prawoto, Eko Cahyo (Journal of Languages and Language Teaching, 2023)
The ability of students to edit scientific papers is still low, especially in mastering the use of hedge (fencing devices) and boosters (strengthening devices). Hedges and boosters are forms of expression of the author's attitude towards propositional content through epistemic modalities. This study aims to describe hedges and boosters in student scientific articles within the framework of a pragmatic metadiscourse. A qualitative descriptive approach was used in this study. The data used is in the form of editing words, sentences, and paragraphs in scientific articles editing courses. The source of this research data is a scientific article by PGRI Adi Buana University Surabaya students in 2022. Data collection techniques use documentation techniques and recording techniques. Data analysis techniques to identify hedges and word lists of boosters using the AntConc application built by Lawrence Anthony. Data that has been obtained from the AntConc application found the frequency of hedges and boosters in scientific articles. The results of this study showed that the use of modal verb hedges in the first position was 214 frequencies, followed by 59 adverbs of hedges, and verb hedges were 3 frequencies, while the use of booster in the first position was 202 frequencies, followed by adverbs booster of 63 frequencies, and booster verbs of 6 frequencies. This study shows that students ability to tendency to (1) use epistemic modalities in modal verbs, (2) tend to use more capital verbs that mean certainty and possibility, and (3) tend to use adverbs to mean epistemic modalities.